Ulcerative Colitis in the Chinese Population of Vancouver, British Columbia - Hugh Chaun; Hugh J Freeman (Canadian Journal of Gastroenterology)
The clinical records of 22 Chinese patients with ulcerative colitis (UC) seen in Vancouver, British Columbia from 1975 to 1989 were reviewed. There was a predominance of males, with a male to female ratio of 1.75:1. The age range at diagnosis was 14 to 67 years (mean 38.9). Eighteen of the 22 patients were immigrants, and one was a visitor from Hong Kong. The age at diagnosis of the three Canadian-born patients (14, 26 and 26 years old) was less than the mean age at diagnosis of the immigrant group. The immigrants had resided in Canada for a mean of 9.3 years before developing symptoms of UC. Despite the rarity of UC in Hong Kong, 59% of the Chinese patients in this series were Hong Kong immigrants. This study demonstrates that UC is not as uncommon a disease in Chinese as had been previously perceived. Adequate time is apparently necessary for exposure to environmental factors in the pathogenesis of UC. The opportunity for continued study of defined ethnic immigrant populations in North America may yield useful information related to environmental factors that may be important in the etiology and pathogenesis of UC.